Linking Safety Culture and Climate to Performance: The Mediating Effect of Psychosocial Hazards among Refinery Workers at PT Kilang Pertamina International - Abdul Kadir Alamudi; Putri Nilam Kencana (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: This study aims to examine the effect of safety climate and safety culture on safety performance and investigate the moderating function of psychosocial hazards.Methodology: The questionnaire was given online using a Google form, and sampling was carried out based on certain criteria through a stratified random sampling method. The Slovin formula was used to get the sample size. This study’s population was 1145; the sample used was 296 PT employees. Kilang Pertamina Internasional in Central Jakarta. The data was analyzed using Partial Least Squares (PLS).Findings: The results of this investigation confirm that safety culture and climate have a significant influence on improving employee safety performance. On the other hand, psychosocial hazards are an essential factor that bridges the relationship, where psychological stress felt by employees can reduce compliance with safety procedures. The findings of this investigation also demonstrate that organizations that build a positive safety culture and climate will be able to reduce psychosocial stress, which ultimately has an impact on increasing employee compliance with safety operational standards.Implications/Novel Contribution: The study highlighted major takeaways for safety managers and safety scholars. Effective safety management depends not only on formal policies and procedures but also on employees’ psychological conditions and workload.